Temperature-dependent electrical characteristics analysis of the Al/p-type Si structures with GO and PTCDA interlayer: structural properties - Berk, Niyazi; Seymen, Halil; Ozerli, Halil; Karatas, Sukru (Springer, 2025)
In this study, the electrical characteristics of Al/p-type Si semiconductor structures with PTCDA and GO interlayer were analyzed using current-voltage (I-V) measurements a wide temperature range (from 80 to 420 K with 20 K intervals and +/- 2.0 V). The ideality factor (n) and barrier height (Phi bo) values changed between 6.398 and 1.330 and 0.221 eV and 0.999 eV (for thermionic emission, TE, method), 0.243 eV and 1.084 eV (for Norde method) in temperature range of 80 K and 420 K, respectively. The experimental findings revealed that values of ideality factors (n), rectification ratio (RR) and series resistance (RS) decreases with increasing temperature, while barrier heights (Phi bo) and saturation currents (I0) values increases with increasing temperature. The Phi bo-n and Phi bo-q/(2kT) curves were obtained to explain the high n values and non-ideal situations of the Richardson curves. Two linear regions were found at low temperatures (from 80 to 180 K) and high temperatures (from 200 to 420 K). Thus, for low and high temperatures, Gaussian distributions (GDs) values of the I - V plot of the Al/(PTCDA:GO)/p-type Si semiconductor structure yielded average barrier heights of 0.7017 and 1.3342 eV with standard deviations (sigma 0) of 83.06 mV and 168.80 mV, respectively. Also, this values of barrier height have also been confirmed by updated ln(I0/T2) - (q2 sigma s2)/(2k2T2) vs. q/(kT) curves, which correspond to two distinct temperature regions. Richardson constant (A*) value with 1.153 x 10-6A/(K2cm2) is lower than the known value of p-type Si. But nevertheless, for distribution 1, Richardson's constant of 80.64 A/(K2cm2) is approximately three times larger than the known theoretical value of 32 Acm-2 K-2 for p-type silicon.
Keywords: Schottky-Barrier; Perylenetetracarboxylic Dianhydride; Interface States; Transport; Height; Diode; Films; Rise